Asymmetric mamillary bodies: MR identification. - Mamourian, A C; Brown, D B (American Journal of Neuroradiology, 1993)
We report three cases in which there was marked asymmetry of the mamillary bodies, noted on MR in two and at autopsy in the third. Based on its proposed pathogenesis, we suggest that this finding could have value in locating temporal lobe disease in patients with intractable epilepsy.